TECHNOLOGY- ENHANCED WORD WALL MEDIA AND ITS IMPACT ON STUDENTS’ WRITING SKILLS : AN ICT- INTEGRATED APPROACH IN EFL CONTEXT - Asriani Hasibuan; Meisa Fitri Nasution; Yusni Sinaga; Elysa Rohayani Hsb; Dini Hariyati Adam; Faridatul Istighfaroh (PT. Jurnal Center Indonesia Publisher, 2026)
This study investigated the impact of technology-enhanced Word Wall media on students’ writing skills in an EFL context. The research aimed to determine whether the use of Word Wall as an ICT-integrated learning media could significantly improve students’ writing performance, especially in writing descriptive text. The study employed a pre-experimental design with one group pre-test and post-test. The sample consisted of 20 eleventh-grade students selected from SMA Negeri 8 Padangsidimpuan. The data were collected through writing composition tests and observation during the learning process. The results showed that the students’ writing performance improved after being taught through Word Wall media. The mean score of the pre-test was lower than the post-test mean score, indicating a positive effect of the treatment. The hypothesis test also showed that the use of Word Wall media had a significant impact on students’ writing skills. It can be concluded that technology-enhanced Word Wall media is effective in supporting students’ writing development and creating more interactive and engaging EFL learning.